Industrial robot applications - Appleton, E. (Open University Press robotics series, 1987)
Using robots successfully in manufacturing industry depends on the process of matching the tasks with the available tools. Here, the engineer has a full account of how this is achieved. The first chapters deal with production engineering considerations, assessing the requirements of both tasks and robots, and the matching process. The core of the book contains a chapter-by-chapter coverage of all the major application areas featuring full case studies which provide the framework for detailed analysis of robot systems and discussion of their capabilities. Actual practice exemplifies points of principle throughout the book, and in addition to the engineering problems, cost, safety and social factors are always kept in view. The final section on implementation provides straightforward guidance on the steps taken to effect a successful robot system installation. For anyone with a robotics application in mind this book wil prove a tool well matched to the task. This book should be of interest to second and third year engineering students and manufacturing engineers.